Association between a mismatch of maternal/neonatal body size and obstetrical interventions in Switzerland in the 1920s: a cross-sectional study (Swiss Medical Weekly, 2025)
INTRODUCTION: Human childbirth remains a complex and risky process for both mothers and infants, even with modern advancements in medical care. This study investigated the prevalence of obstetric interventions, namely caesarean sections, episiotomies, and forceps deliveries, along with the role of maternal-foetal body size mismatch in influencing delivery outcomes.METHODS: Utilising two datasets from similar archival sources in two Swiss cities (Basel and Lausanne) from the 1920s, we explored the relevance of a mismatch between the body size of the mother and the foetus as a risk factor for obstetrical interventions and the duration of the expulsion phase during delivery.RESULTS: Over 91% of births (1290/1407 in Basel and 1062/1145 in Lausanne) featured the foetal head in a normal position (either the right or left occiput anterior position). Episiotomies were performed in 8–17% of cases (233/1407 in Basel and 98/1145 in Lausanne) and forceps deliveries in 1–5% (17/1407 in Basel and 54/1145 in Lausanne). Caesarean sections were rare (